Overman Rearrangement of Fluorinated Allylic Alcohols as a Key Step for the Synthesis of Glycyldecylamide (GDA) Mimics - Ramb, Daniel C.; Haufe, Günter (Synlett, 2013)
Overman rearrangements based on secondary 2-fluoroallylic alcohols were performed to synthesize fluorinated primary allylic amines for the first time. The vinylic fluorine atom dramatically slows down the reaction rate. Long alkyl chain fluorinated allylic amine, which is a mimic of a drug against schizophrenia, was further coupled with Boc-protected phenyl glycine, forming a Gly-Phe peptide mimic.
Keywords: allylic amines; fluorinated building blocks; alcohols; Overman rearrangement; peptide mimics